2012
DOI: 10.1007/s00296-012-2610-2
|View full text |Cite
|
Sign up to set email alerts
|

The importance of rheumatology biologic registries in Latin America

Abstract: Rheumatoid arthritis is a systemic inflammatory disorder characterized by joint articular pain and disability. Although there is scarcity of data available on the incidence and prevalence of RA in Latin America, there is a growing recognition of this disease where chronic diseases are on the rise and infectious disease on the decline. RA is a substantial burden to patients, society, and the healthcare system. The heterogeneity identified within RA presents an opportunity for personalized medicine, especially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…In the USA, the American College of Rheumatology launched the RISE registry in 2014, in which data are extracted from electronic medical records used by rheumatology practices. However, challenges remain in implementing post-approval surveillance in countries that lack registries or that fail to maintain and update their existing registries [25].…”
Section: A Risk Management Plan (Rmp) For Approved Biosimilarsmentioning
confidence: 99%
“…In the USA, the American College of Rheumatology launched the RISE registry in 2014, in which data are extracted from electronic medical records used by rheumatology practices. However, challenges remain in implementing post-approval surveillance in countries that lack registries or that fail to maintain and update their existing registries [25].…”
Section: A Risk Management Plan (Rmp) For Approved Biosimilarsmentioning
confidence: 99%
“…From 813 abstracts, we selected 309 publications from 36 registers. Sixteen published reviews allowed us to identify 7 other registries with no publication identified in databases (hand search) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…El primer reporte fue llevado a cabo en 2011, donde se analizaron 966 pacientes (543 casos y 423 controles), que recibieron 1132 ciclos de tratamientos con agentes biológicos en 56 centros de salud entre el 1º de agosto de 2010 y el 1º de abril de 2011 21,22 .…”
Section: Darío Scublinskyunclassified